Regulation of Flowering and post Harvest Behaviour of Tuberose (Polianthes Tuberosa L.) - Shiji K Itty (Department of Pomology and Floriculture, College of Horticulture, 2001)
A study was undertaken at the College of Horticulture, Kerala Agricultural University, Vellanikkara, Thrissur during the year 1998-2000 to determine the effect of bio regulators on the growth and flowering of tuberose. Experiments were also conducted to standardize pulsing and holding solutions in tuberose. The treatments, In general, significantly influenced all the morphological, floral and bulb characters. The height reduction was found to be maximum with paclobutrazol 100 ppm applied at 60 DAP and 200 ppm applied 30 DAP. Highest plant spread was given by CCC bulb dip treatment. Paclobutrazol and BA bulb dip caused a significant increase in the number of leaves. Bulbs dipped in CCC 1000 ppm, BA 50 and 100 ppm produced longer leaves, when compared to control. Maximum tiller production was noticed in bulbs treated with CCC 1000 ppm. But, in later stages of growth, BA 50 'ppm applied 60 days after planting gave more tillers. Paclobutrazol applied 60 DAP, reduced the days required for the emergence of spike. Paclobutrazol 200 ppm applied 60 DAP recorded earlier floret opening, while, BA showed delayed opening. Longer spikes were produced by BA treatments. The longest rachis was obtained with paclobutrazol 200 ppm applied at flowering. In the case of number of florets per spike, paclobutrazol applied as bulb dip was found to be the best.